2009
DOI: 10.1128/aac.00268-09
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Aerosol MP-376, a Levofloxacin Inhalation Solution, in Models of Mouse Lung Infection Due toPseudomonas aeruginosa

Abstract: Progressive respiratory failure due to Pseudomonas aeruginosa is the leading cause of morbidity and mortality in patients with cystic fibrosis. The pulmonary delivery of antimicrobial agents provides high concentrations of drug directly to the site of infection and attains pharmacokinetic-pharmacodynamic indices exceeding those which can be achieved with systemic dosing. MP-376 is a new formulation of levofloxacin that enables the safe aerosol delivery of high concentrations of drug to pulmonary tissues. In vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 29 publications
0
27
0
1
Order By: Relevance
“…As summarized in Table 1, the MIC 90 value of ciprofloxacin and levofloxacin for aggregated CF isolates is 8 mg/liter; early colonizers should be more susceptible, while isolates from chronically infected patients should have higher MIC values. An in vitro study (215) and an in vivo mouse lung infection model (216) revealed that levofloxacin exhibited a concentrationor dose-dependent reduction of viable P. aeruginosa counts. Aerosolized levofloxacin doses of 15, 30, and 60 mg/kg of body weight in a chronic lung infection model reduced viable counts by 0.07, 0.62, and 1.25 CFU/lung, whereas the antibacterial effects of intraperitoneally applied identical doses of levofloxacin were significantly lower.…”
Section: Preclinical and Clinical Pk/pd Studies In Cf Patientsmentioning
confidence: 99%
See 3 more Smart Citations
“…As summarized in Table 1, the MIC 90 value of ciprofloxacin and levofloxacin for aggregated CF isolates is 8 mg/liter; early colonizers should be more susceptible, while isolates from chronically infected patients should have higher MIC values. An in vitro study (215) and an in vivo mouse lung infection model (216) revealed that levofloxacin exhibited a concentrationor dose-dependent reduction of viable P. aeruginosa counts. Aerosolized levofloxacin doses of 15, 30, and 60 mg/kg of body weight in a chronic lung infection model reduced viable counts by 0.07, 0.62, and 1.25 CFU/lung, whereas the antibacterial effects of intraperitoneally applied identical doses of levofloxacin were significantly lower.…”
Section: Preclinical and Clinical Pk/pd Studies In Cf Patientsmentioning
confidence: 99%
“…In a mouse lung infection model comparing aerosolized tobramycin and levofloxacin, it was shown that bacterial loads of P. aeruginosa in the lungs of chronically infected animals were reduced following twice-daily treatment for 3 days with 60 mg/kg of levofloxacin or tobramycin by 3.33 log 10 titers and 2.94 CFU/lung, respectively, compared to the preexposure level (216).…”
Section: Preclinical and Clinical Pk/pd Studies In Cf Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, compared to aztreonam and tobramycin, in a model of acute lethal lung infection, levofloxacin produced the greatest decrease in the amount of CFU per lung. Surprisingly, levofloxacin also provided the highest survival rate (100%) compared to tobramycin (60%) and aztreonam (20%) (165). The reason for this dramatic difference in survival is unclear, and few animal studies have evaluated both PK and survival as they relate to the treatment of induced infections with inhaled antibiotics, especially in neutropenic animals.…”
Section: Animalsmentioning
confidence: 99%